Kinerja Keuangan dan Faktor Lainnya yang memengaruhi Nilai Perusahaan non-Keuangan di BEI - Mutiara Mayang Sari; Indra Arifin Djashan (Media Bisnis, 2022)
The purpose of this study is to obtain empirical evidence regarding the effect of dividend policy, liquidity, profitability, leverage, firm size, firm age, firm growth on firm value. This Study uses a sample of non-financial companies listed on the Indonesia Stock Exchange (IDX) in the period 2018-2020. The sample selection in this study uses a judgement sampling method by setting five sample criteria, so that the sample obtained is 288 companies. In testing hypothesis, this research uses multiple regression method. The results of this study conclude that the variables of profitability have a positive effect on firm value and variables firm growth has negative effect on firm value, but the variables of dividend policy, liquidity, leverage, firm size, firm age have no effect on earnings management.